ASSESMENT OF DETERMINANTS OF EFFCTIVE CHANGE IMPLEMENTATION IN THE COUNTY GOVERNMENTS: A CASE OF LAIKIPIA COUNTY - Gichuki, Evah Wangui; Abok, Dr. Alice (IJRDO - Journal of Business Management, 2015)
Public sectors worldwide are under pressure to increase efficiency while delivering improved and integrated services. The purpose of the study was to examine the factors influencing effective change implementation in the county governments a case study of Laikipia County with aim of making recommendations on effective change implementation. The study was aimed at establishing how top management support, communication, technology tools, and government policies affect effective change implementation. The study employed descriptive research design. A sample of 212 Laikipia County Government employees was selected through stratified random sampling to participate in the study. Self-administered questionnaires were used to collect data which was analyzed using SPSS versions 20 and presented in form of relevant graphs and tables. Most of the respondents agreed with the statement that top management participates in ensuring successful delivery of services under the new changes. Results showed that most of the respondents agreed that top management delegates and monitors duties on ensuring change management to ensure success. Most of the respondents agreed that government employment policy and regulations affect effective implementation of change in the County. Transition guidelines on devolution influences change implementation in Laikipia County Government was supported by most of the respondents while close to half agreed with presence of adequate legal framework to support the implementation of change. The County Governments have a great responsibility of ensuring that top management plays its role in effective change implementation which is vital. To achieve this, proper and extensive monitoring activities in change implementation should be provided to ensure its effectiveness .